Geoprocessing applied to geo-environmental analysis in the Municipality Of Vitória da Conquista-Bahia - de Andrade-Oliveira, Débora Paula (2018)
The purpose of this study was to analyze the geoenvironmental characteristics in the city of Vitória da Conquista through geoprocessing, especially with the use of remote sensing and SIG, in order to present potential subsidies to environmental planning for the municipality. At the methodological level, we performed a theoretical discussion and, in parallel, the design and preparation of the project chartplotter and the empirical analysis. The geographical data used was the basis vector shapefile format and the data rasters, with images of the Landsat 8 satellite and the SRTM radar, both entered and processed in the free software of Geographic Information System QGIS, and the coordinate reference system used was the SIRGAS 2000 UTM 24S. The environments have potential and specific weaknesses that need to be considered in the process of land use and occupation, which requires a city planning that is more effective and consistent with local reality.